Can marine cloud brightening reduce coral bleaching?. (20th June 2013) - Latham, John; Kleypas, Joan; Hauser, Rachel; Parkes, Ben; Gadian, Alan
Abstract: Increases in coral bleaching events over the last few decades have been largely caused by rising sea surface temperatures (SST), and continued warming is expected to cause even greater increases through this century. We use a Global Climate Model to examine the potential of marine cloud brightening (MCB) to cool oceanic surface waters in three coral reef provinces. Our simulations indicate that under doubled CO2 conditions, the substantial increases in coral bleaching conditions from current values in three reef regions (Caribbean, French Polynesia, and the Great Barrier Reef) were eliminated when MCB was applied, which reduced the SSTs at these sites roughly to their original values .